Association between sex hormones and anti-S/RBD antibody responses to COVID-19 vaccines in healthcare workers - Simona Anticoli; Maria Dorrucci; Elisabetta Iessi; Flavia Chiarotti; Reparata Rosa Di Prinzio; Maria Rosaria Vinci; Salvatore Zaffina; Vincenzo Puro; Francesca Colavita; Klizia Mizzoni; Silvia Meschi; Nicoletta Vonesch; et al. (Human Vaccines & Immunotherapeutics)
Healthcare workers (HCWs) are the target population for vaccination against coronavirus disease (COVID-19) as they are at a high risk of exposure and transmission of pathogens to patients. Neutralizing antibodies developed after COVID-19 vaccination decline within few months of vaccination. Several factors, including age and sex, can affect the intensity, efficacy, and duration of immune response to vaccines. However, sex-specific analyses of humoral responses to COVID-19 vaccines are lacking. This study aimed to evaluate sex-based differences in anti-S/RBD (Receptor Binding Domain) responses at three different time points after the second dose of mRNA COVID-19 vaccine in HCWs in relation to age, and to investigate the role of sex hormones as potential markers of response. Anti-S/RBD levels after two doses of the mRNA vaccine were collected from 521 HCWs naïve to COVID-19, working at two Italian Clinical Centers. Multiple regression analysis was applied to evaluate the association between anti-S levels and sex, age, and plasma levels of sex hormones. Significantly higher anti-S/RBD response to the COVID-19 vaccination was found in female HCWs, and a significant and more abrupt decline in response with time was observed in women than that in men. A novel, positive association of testosterone plasma levels and higher anti-S levels in male HCWs was found, suggesting its potential role as sex specific marker in males. In conclusion, understanding the sex-based differences in humoral immune responses to vaccines may potentially improve vaccination strategies and optimize surveillance programs for HCWs.